PEMAHAMAN KUALITATIF SISWA KELAS VII PADA KONSEP MASSA JENIS - Winarsi; Mansyur, Jusman (Universitas Tadulako, 2021)
This study uses a qualitative descriptive approach that aims to describe students' qualitative understanding on density. This research was conducted at SMP Labschool UNTAD Palu. The subjects of this study were students of grade 7th with a total of 15 students. The research instrument used was the respondent selection test, the density concept understanding test and interviews. The respondent selection test consisted of 25 questions given to 15 students to determine 6 respondents and the essay test on understanding the density concept consisted of 5 questions given to 6 selected respondents. Based on the results of the study, it shows that students' qualitative understanding of the concept of density is still low where only some understand and some do not understand and experience misconceptions, the ability of each indicator of students' conceptual understanding, including translation was still not good, indicators of understanding the concept of interpretation are still not good and indicators of understanding the concept of interpretation are still not good. understanding of the concept of extrapolation is also still lacking and the qualitative understanding of respondents in the high category shows a better qualitative understanding than the respondents in the medium and low categories and the qualitative understanding of the respondents in the medium and low categories tends to show the same results.